(untitled) (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Fitriadi R, Palupi M, Azhari RF, Candra RA, Sukardi P. 2023. Short Communication: Distribution and diversity of Gastropods in the rice-fish farming system. Biodiversitas 24: 2006-2012. The rice-fish farming system is a planting system that combines paddy fields and fish farming. Combining these activities aims to maximize the potential for land use and increase farmers’ income. The process of decomposing metabolic waste produced by fish and rice plants requires the help of decomposer organisms such as bacteria or gastropods. Apart from their nature which sometimes becomes a rice pest, gastropods also have an important role in an aquatic environment as detritivores. This study aimed to determine the composition of the gastropods in Panembangan Village and determine the physical factors of the waters in seeking information on the condition of rice-fish farming system rice fields, which were in good or unfavorable condition. The results showed that five species of gastropods were found at the four sampling stations in Panembangan Village, namely Pomacea canaliculate, Melanoides tuberculate, Radix rubiginosa, Pila ampullacea, and Melanoides turricula. The Gastropod diversity index ranged from 0.75-1.11, uniformity values ranged from 0.68-0.80, and dominance index values ranged from 0.38-0.51. As for the physical and chemical parameters of the waters, the quality of the waters at the four sampling stations still supports the life of organisms.